The relationship between stress, resilience and psychological distress among individuals experiencing involuntary job loss - Nurul Izzaty Asyikin Zulkifly (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Involuntary job loss is a stressful life event that increases individuals' psychological distress and detrimental to psychological health. Despite the negative impacts of involuntary job loss, some individuals were able to maintain their distress at a lower level. This study aims to investigate the relationship between psychological distress and its underlying factors, stress (i.e. stress appraisal and financial strain) and resilience among individuals experiencing involuntary job loss in Malaysia. It was hypothesised that i) there are significant relationships between stress and psychological distress; ii) there is a negative relationship between resilience and psychological distress and; ii) resilience moderate the relationship between stress and psychological distress. The self-report questionnaire consisted of four scales measuring stress appraisals (i.e. negative and positive perception of stress), financial strain (i.e. financial distress, financial awareness, and debt-dependence), resilience, and psychological distress was used. Using snowball and convenient sampling, a total of 229 participants who were laid off and unemployed within one month to three years took part in this study. The results from hierarchical multiple regression show significant relationships between stress (stress appraisal and financial strain) and psychological distress as well as the negative relationship between resilience and psychological distress. However, the results only discover the moderation effects of resilience on the negative perception of stress and debt-dependence. The results supported stress as the contributor to psychological distress and resilience buffers psychological distress following job loss. This study also discusses the research findings within the Malaysian context, as well as highlighting the limitations and recommendations for future research